(untitled) (Research, Society and Development, 2021)
To analyze published scientific evidence on the knowledge and use of contraception in adolescence: contributions from nursing care. This study is a literature review of the integrative literature review method, carried out in the months between March and August 2021. The search was carried out through the Virtual Health Library Platform - VHL, using the LILACS, BDENF databases , through SCIELO. Adhering through the descriptors/key words: “Nursing Care”, “Contraceptional”, “Adolescent”, “Health Education”, combined with the Boolean operator “AND”. The role of nurses as health educators working in basic health units, among other social spaces such as schools, properly trained for the educational function, helping adolescents in the process of knowledge construction and its use for self-care. health education actions addressing topics such as sexuality, contraceptive methods and STIs, HIV and AIDS are considered an important tool in health promotion and disease prevention. It is necessary to build critical knowledge of adolescents in relation to their health, favoring them with the empowerment of taking care of themselves, making them responsible for maintaining their health and preventing STIs and unwanted pregnancy. Adequate knowledge about the various contraceptive methods available to young people is of great importance so that the best choice is made, adapting it to socioeconomic conditions, sexual behavior, in addition to assisting in the correct use.